1988
DOI: 10.1177/107110078800800502
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Characteristics of the Collateral Ligaments of the Human Ankle Joint

Abstract: In the present study, the tensile mechanical properties of all of the collateral ligaments of the human ankle joint were determined, in vitro, from tensile tests conducted on 120 ligaments obtained from 20 fresh lower limbs. The ultimate load of the lateral collateral ligaments increased in an anteroposterior sequence, with the anterior fibulotalar ligament less than the fibulocalcaneal ligament and less than the posterior fibulotalar ligament. For the medial collateral ligaments, the increasing order of ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
212
7
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(237 citation statements)
references
References 30 publications
14
212
7
4
Order By: Relevance
“…N. A.; MORENO, T. R.; IBARRA, M. C.; GIESEN, F. L.; CAPURRO, S. B.; El LTFP es el que lo sigue en longitud, con el mayor valor (30mm) descrito por Sarrafian y el menor (21,16mm) por Siegler et al (1988).…”
Section: Discussionunclassified
“…N. A.; MORENO, T. R.; IBARRA, M. C.; GIESEN, F. L.; CAPURRO, S. B.; El LTFP es el que lo sigue en longitud, con el mayor valor (30mm) descrito por Sarrafian y el menor (21,16mm) por Siegler et al (1988).…”
Section: Discussionunclassified
“…Siegler et al [20] reported the tensile mechanical properties of the collateral ligaments of the ankle joint. The Young's modulus of tibiofibular interosseous membrane was estimated according to the ultimate tensile stress and strain at rupture [21].…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…The material properties of all tissues were assigned according to previous simulations or experimental reports [2, [12][13][14][16][17][18][19][20][21]. Bones and cartilages were idealized as being homogeneous, isotropic, and linearly elastic.…”
Section: Finite Element Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Die höchsten Werte -bis zu 3 mm -treten entlang der medialen Kante der Trochlea auf, ein weiteres Maximum findet sich im Zentrum der lateralen Seitenfläche. Eine Untersuchung der Spaltlinien [14] [31].…”
Section: Sprunggelenkeunclassified